Room-temperature testing for high critical-current-density Josephson junctions. - O'Hara, M.J (IEEE Transactions on applied superconductivity)
This paper demonstrates that room-temperature resistance measurements can accurately predict the critical current and normal resistance of high critical-current-density junctions. We fabricated high critical-current-density (~200 μA/μm2=20 kA/cm2) Nb/Al/AlOx/Nb Josephson junctions in cross-bridge Kelvin resistor (CBKR) test structures and measured their electrical characteristics both at 4.2 K and at room temperature. We developed a two-dimensional mathematical model of the CBKR test structure with two resistive wiring layers in order to characterize the effect of current crowding on the room-temperature measurements. We then used the model to remove the effect of current crowding from the room-temperature measurements and correlated the values of these measurements to the electrical properties of the junctions at 4.2 K. We also identified test-structure-design rules that guarantee current crowding is negligible